The Use of Deep Learning for Segmentation of Bone Marrow Histological Images - Oszutowska–Mazurek, Dorota; Knap, Oktawian (Artificial Intelligence Trends in Intelligent Systems, 2017)
Proposed solution gives the segmentation of bone marrow histological images, required for further analysis via different methods. Proposed algorithm is based on deep learning using Convolutional Neural Network. More then 50 of ConvNNs where tested with different configurations and learning parameters (learning rate, weight decay). Obtained effectiveness is more then 92%.